Comparison of Estimated Torques Using Low Pass Filter and Extended Kalman Filter for Induction Motor Drives - Ibrahim Mohd Alsofyani; Nik Rumzi Nik Idris; Yahya A. Alamri; Tole Sutikno; Aree Wangsupphaphol; Norjulia M. Nordin (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
Torque calculation process is one of the major concerns for controlling induction motors in industry, which requires very accurate state estimation of unmeasurable variables of nonlinear models. This can be solved if the variables used for torque calculation is accurately estimated.  This paper presents a torque calculation based on a voltage model represented with a low-pass filter (LPF), and an extended Kalman filter (EKF). The experimental results showed that the estimated torque at low speed based on EKF is more accurate in the expense of more complicated and larger computational time.